Sign Singularity of the Local Energy Transfer in Space Plasma Turbulence - Sorriso-Valvo, Luca; De Vita, Gaetano; Fraternale, Federico; Gurchumelia, Alexandre; Perri, Silvia; Nigro, Giuseppina; Catapano, Filomena; Retinò, Alessandro; Chen, Christopher H. K.; Yordanova, Emiliya; Pezzi, Oreste; Chargazia, Khatuna; et al. (Frontiers in Physics, 2019)
In weakly collisional space plasmas, the turbulent cascade provides most of the energy that is dissipated at small scales by various kinetic processes. Understanding the characteristics of such dissipative mechanisms requires the accurate knowledge of the fluctuations that make energy available for conversion at small scales, as different dissipation processes are triggered by fluctuations of a different nature. The scaling properties of different energy channels are estimated here using a proxy of the local energy transfer, based on the third-order moment scaling law for magnetohydrodynamic turbulence. In particular, the sign-singularity analysis was used to explore the scaling properties of the alternating positive-negative energy fluxes, thus providing information on the structure and topology of such fluxes for each of the different type of fluctuations. The results show the highly complex geometrical nature of the flux, and that the local contributions associated with energy and cross-helicity nonlinear transfer have similar scaling properties. Consequently, the fractal properties of current and vorticity structures are similar to those of the Alfvénic fluctuations.